Synthesis of mono- and few-layered n-type WSe2 from solid state inorganic precursors. Issue 42 (3rd October 2022) - Och, Mauro; Anastasiou, Konstantinos; Leontis, Ioannis; Zemignani, Giulia Zoe; Palczynski, Pawel; Mostaed, Ali; Sokolikova, Maria S.; Alexeev, Evgeny M.; Bai, Haoyu; Tartakovskii, Alexander I.; Lischner, Johannes; Nellist, Peter D.; et al.
Abstract : Tuning the charge transport properties of two-dimensional transition metal dichalcogenides (TMDs) is pivotal to their future device integration in post-silicon technologies. Abstract : Tuning the charge transport properties of two-dimensional transition metal dichalcogenides (TMDs) is pivotal to their future device integration in post-silicon technologies. To date, co-doping of TMDs during growth still proves to be challenging, and the synthesis of doped WSe2, an otherwise ambipolar material, has been mainly limited to p-doping. Here, we demonstrate the synthesis of high-quality n-type monolayered WSe2 flakes using a solid-state precursor for Se, zinc selenide. n-Type transport has been reported with prime electron mobilities of up to 10 cm 2 V −1 s −1 . We also demonstrate the tuneability of doping to p-type transport with hole mobilities of 50 cm 2 V −1 s −1 after annealing in air. n-Doping has been attributed to the presence of Zn adatoms on the WSe2 flakes as revealed by X-ray photoelectron spectroscopy (XPS), spatially resolved time of flight secondary ion mass spectroscopy (SIMS) and angular dark-field scanning transmission electron microscopy (AD-STEM) characterization of WSe2 flakes. Monolayer WSe2 flakes exhibit a sharp photoluminescence (PL) peak at room temperature and highly uniform emission across the entire flake area, indicating a high degree of crystallinity of the material. This work provides new insight into the synthesis of TMDs with charge carrier control, to pave the way towards post-silicon electronics.